Exploring the Relationship Between Clostridium thermocellum JN4 and Thermoanaerobacterium thermosaccharolyticum GD17 - Wang, Fangzhong; Wang, Mingyu; Zhao, Qi; Niu, Kangle; Liu, Shasha; He, Didi; Liu, Yan; Xu, Shiping; Fang, Xu (Frontiers in Microbiology, 2019)
Characterizing and engineering microbial communities for lignocellulosic biofuel production has received widespread attention. Previous research has established that Clostridium thermocellum JN4 and Thermoanaerobacterium thermosaccharolyticum GD17 coculture significantly improves overall cellulosic biofuel production efficiency. Here, we investigated this interaction and revealed the mechanism underlying the improved efficiency observed. In contrast to the previously reported mutualistic relationship, a harmful effect toward C. thermocellum JN4 was observed in these microbial consortia. Although T. thermosaccharolyticum GD17 relieves the carbon catabolite repression of C. thermocellum JN4 regarding obtaining more cellobiose or glucose released from lignocellulose, T. thermosaccharolyticum GD17 significantly hampers the growth of C. thermocellum JN4 in coculture. The increased formation of end products is due to the strong competitive metabolic advantage of T. thermosaccharolyticum GD17 over C. thermocellum JN4 in the conversion of glucose or cellobiose into final products. The possibility of controlling and rebalancing these microbial consortia to modulate cellulose degradation was achieved by adding T. thermosaccharolyticum GD17 stimulants into the system. As cellulolytic bacteria are usually at a metabolic disadvantage, these discoveries may apply to a large proportion of cellulosic biofuel-producing microbial consortia. These findings provide a reference for engineering efficient and modular microbial consortia for modulating cellulosic conversion.